The influence of translucent barriers on the effectiveness of dental light curing (Research, Society and Development, 2021)
The aim of the present study was to evaluate the irradiance of different light-curing devices when subjected to the use of different types of biological protection barriers. The tested devices were: Bluephase N. Radii-Cal and VALO wireless. The biosafety barriers were: Polyethylene and Polyvinyl Chloride with one and two turns. The tips of the devices had their diameters measured on a digital pachymeter and the area of each tip was calculated. The power (mW) of the devices was measured with a potentiometer for 20 seconds and three times for each device. Then. the irradiance (mW / cm²) was calculated by the quotient of the power of the device by the cross-sectional area of the tip of the photoactivator. The irradiance data for each group were collected and subjected to two-way ANOVA analysis of variance (SPSS). with Tukey's post-hoc. As a result. a statistically significant interaction between the different types of light-curing device and translucent protection barriers (p < 0.05) were observed. It can be concluded that the protective barrier made with 1-turn polyvinyl chloride demonstrated the best irradiance results and among the light-curing devices. regardless of the type of barrier used. Bluephase obtained the best irradiance results. followed by Valo and Radii.